THE EFFECT OF THE ONLINE-BASED M-APOS MODEL ON MATHEMATICS PROBLEM-SOLVING ABILITY REVIEWED FROM STUDENT'S SELF-ESTEEM - Mahalul Ilmi; Makmuri Makmuri; Eti Dwi Wiraningsih (JURNAL TARBIYAH, 2022)
Mathematics is a difficult subject for most students, where students tend not to be able to solve problems on questions in the form of problem-solving such as description questions. Efforts can be made to increase student learning outcomes by applying the M-APOS learning model. This study investigates whether or not there is a significant effect of the M-APOS learning model on mathematical problem-solving abilities in terms of the self-esteem of East Jakarta Vocational School students Region II, 2021-2022 academic year. This study is an experimental study that compares the value of the experimental class using the M-APOS model with the value of the control class using the conventional model. The values are analyzed using the t-test, where the results of the t-test indicate that ????count = 15.736 and df= 82. Besides it was found that ????????????????e = 1.989. The test criteria are that the ????0 is rejected if ????count > ????????????????e and it was found that 15.736 > 0.165. Based on the test results, the ????0 is rejected. This means that there are differences in the mathematical problem-solving abilities of students who receive the M-APOS learning model and those who receive conventional learning models.